Iran : a very short introduction - Ansari, Ali M. ([Oxford] : Oxford University Press, 2014)
Ali Ansari provides a radical reinterpretation of Iranian history and politics, placing the Islamic Revolution in the context of a century of political change and social transformation, to gain a fuller understanding of Iran's identity, culture, and politics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 11, 2014).
Keywords: Iran -- History